2018
DOI: 10.3390/en11113179
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Energy Renovation on the Change of Indoor Temperature and Energy Use

Abstract: The aim of the renovation of apartment buildings is to lower the energy consumption of those buildings, mainly the heating energy consumption. There are few analyses regarding those other energy consumptions which are also related to the primary energy need for calculating the energy efficiency class, including the primary energy need of calculated heating, domestic hot water (DHW), and household electricity. Indoor temperature is directly connected with heating energy consumption, but it is not known yet how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…In comparison of the energy performance on the basis of variation of total delivered energy we can see that differences were relatively small because the energy for space heating was one of the smallest components of total energy use. However, it is important to see that in calculations indoor temperature set point was 21 • C. It was shown by preceding studies [67][68][69] that indoor temperature set point used is higher, typically 22 • C for post-renovation situation. That a 1 • C rise will affect the amount of delivered energy for space heating in average +33%, EPV for +1.2-+1.4% and the global cost for +1.0-+1.3%.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison of the energy performance on the basis of variation of total delivered energy we can see that differences were relatively small because the energy for space heating was one of the smallest components of total energy use. However, it is important to see that in calculations indoor temperature set point was 21 • C. It was shown by preceding studies [67][68][69] that indoor temperature set point used is higher, typically 22 • C for post-renovation situation. That a 1 • C rise will affect the amount of delivered energy for space heating in average +33%, EPV for +1.2-+1.4% and the global cost for +1.0-+1.3%.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that room-based ventilation units in Estonian apartment buildings are not ensuring the necessary air change rate [3,7,18]. Mikola et al [3] point out that as these room units generate high sound power level, people switched ventilation units to the 30% of the maximum airflow.…”
Section: Discussionmentioning
confidence: 99%
“…In Estonia, multi-story apartment buildings constitute about 60% of the whole dwelling stock, and the majority (75%) of the buildings were built primarily in 1961-1990 [1]. Due to the increase in the price of energy, the energy policies of the European Union [2], the age, construction quality, and poor thermal insulation of the buildings, as well as both morally and technically outdated, obsolete heating and ventilation systems, there is an increasing need for retrofitting [3][4][5][6][7]. Part of the building stock built before the 1990s has already been renovated but for many apartment buildings this process is yet to start [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of measured real energy use and energy use predicted by calculations have shown that the energy performance gap is larger for more energy efficient buildings [3]. This could be partly caused by user behaviour [4,5].…”
Section: Introductionmentioning
confidence: 99%